A Review on Theranostics: An Approach to Targeted Diagnosis and Therapy - Shrivastava, Saumya; Jain, Saloni; Kumar, Deepak; Soni, Shankar Lal; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Emerging as a targeted, safe, and efficient pharmacotherapy is the approach of theranostics, which focuses on patient centered care. It is a combination of diagnosis and therapeutics. Theranostics is a new field of medicine which combines specific targeted therapy based on specific targeted diagnostic tests. With a key focus on patient centered care, theranostics provides a transition from conventional medicine to a contemporary personalized and precision medicine approach. The theranostics paradigm involves using nanoscience to unite diagnostic and therapeutic applications to form a single agent, allowing for diagnosis, drug delivery and treatment response monitoring. The theranostics medicine can achieve systemic circulation, evade host defenses and deliver the drug and diagnostic agents at the targeted site to diagnose and treat the disease at cellular and molecular level.